Ulama Cadre Formation in the Digital Era: Development of Ma'had Aly Curriculum Based on Knowledge and Social Context - Subhan Yahya , Moch.; Padil , Moh; Aminatuz Zuhriyah , Indah; Zainuddin, Zainuddin (LP3M UNZAH GENGGONG, 2025)
This research examines the development of the Ma'had Aly curriculum for ulama cadre formation in the digital era, focusing on integrating classical Islamic knowledge with contemporary societal demands. The study is driven by the rapid digital transformation and the growing need for Islamic scholars who can address both traditional religious teachings and modern challenges. As an Islamic higher education institution, Ma'had Aly plays a crucial role in producing competent ulama equipped for both religious guidance and engagement with current issues. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observations, and document analysis involving administrators, lecturers, kyai, alumni, and stakeholders. The findings show that Ma'had Aly continually updates its curriculum by blending classical texts with contemporary knowledge, emphasizing digital literacy and social engagement. The application of Outcome-Based Education (OBE) and Constructive Alignment ensures that graduates acquire both theoretical understanding and practical skills necessary in today's society.Active stakeholder involvement especially kyai, lecturers, and external religious bodies plays a vital role in shaping the curriculum to meet the expectations of both religious and public spheres. Additionally, integrating digital tools into the curriculum is highlighted as essential for preparing graduates for the demands of the digital age. This study offers valuable insights into curriculum development at Ma'had Aly, contributing recommendations to ensure its continued relevance and leadership in Islamic higher education amidst ongoing societal changes.